Conditions of the Kingdom of Jerusalem during the reign of Queen Melisende (525-548 AD / 1130-1153 AD) (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
Queen Melisende had the qualities of strength and courage, so she was classified as one of the most important queens who reigned on the throne of power in the Arab-Islamic East, at a time when Europe suffered from bad conditions that included various aspects of life. That period was described as the worst for Europe and was called the Middle ages, Queen Melisende proceeded to entering the world of politics and government as the heir to the throne of her father Baldwin ll, she leaned strongly on the science of events and not did not excel in politics only in the military field, she was distinguished and courageous and Queen Melisende rose in conjunction with her husband colonel V of Anjou to the throne of the kingdom Jerusalem from the year 525 AH / 1133 AD to the year 548 AH/1153 AD, after the death of her father Baldwin ll. She was also responsible for the proposal of her son Baldwin lll between the years 548 AD/1153 AD and the year 552 AD/1161 AH, and she entered into a conflict with him over the throne after trying to monopolize power, but in the end she was forced to give up the righteous throne was granted to her son Baldwin lll, and to reside in the fiefdom Nablus for life.